A emergência da educação infantil e o trabalho docente: um estudo da rede pública de ensino no norte do Tocantins - Arinalda Silva Locatelli (2018)
We understand that the definition of the importance of Early Childhood Education, present in the legal bases, through numerous documents published in the last two decades, as well as the important changes in the construction of the public policy of Early Childhood Education, brought many other challenges, requiring new assessments and new answers. Our objective, then, was to analyze the work and the teaching profession in Early Childhood Education, considering the process of expansion of educational policies for this stage of basic education and the reality of teachers (teachers and monitors) in municipal schools in the northern region of the state of Tocantins. We orient ourselves by the sociological perspective of the work, this means to say that we understand it as a historical and social construction, that occurs in a context of conflicts and tensions. As a methodological path, the study proposed the realization of a dialectical approach to the thematic, adopting the quantitative-qualitative method of analysis. The research came from two analytical categories, work and profession, organized in two thematic axes: 1) teaching as a work and 2) teaching as a profession. The first axis focused on the most objective aspects of teaching, involving discussions about the activities developed, the resources and the infrastructure that the teachers have and how their professional careers are structured in terms of hiring, remuneration and progression. The second axis analyzed its more subjective aspects, involving discussions such as teacher professionalism, feminization and feminization of teaching and care as a social category in Early Childhood Education. The field of research was the micro-region of Bico do Papagaio, located in the north of the state of Tocantins, focusing on two of its municipalities, Tocantinópolis and Araguatins. The research was based on two types of sources: documentary and empirical. For the first, official documents were analyzed, with different levels of coverage, having as temporal delimitation the last two decades. As for the empirical source, we used interviews conducted with the Municipal Secretaries of Education of the chosen municipalities, with the Managers or responsible for the schools visited and the questionnaires applied to 137 teaching subjects active in children's education classes in the rural and of the cities mentioned. We start from the understanding and verification that there is an emergency of Early Childhood Education as an educational policy, attested by its legal reordering, which establishes this stage of education as a right of the child, with a framework for expanding care for children from 0 to 5 years in the last two decades. In this sense, our thesis is that the attainment of this right is being implemented in a context in which professional valorization and working conditions do not take place at the same time. This fact creates obstacles for these professionals to increase their ability to influence their own pedagogical practice and their career, as well as for them to be individually and socially constituted as members of the professional body of the teaching profession